2022
DOI: 10.3389/feduc.2022.976791
|View full text |Cite
|
Sign up to set email alerts
|

Not useful to inform teaching practice? Student teachers hold skeptical beliefs about evidence from education science

Abstract: A goal of teacher education is to promote evidence-based teaching. Teacher beliefs are assumed to act as facilitators or barriers to evidence-based thinking and practices. In three sub-studies with a total of N = 346 German student teachers, the extent of student teachers’ beliefs about education science and their consequences and sources were investigated. First, the results of questionnaire data indicated that student teachers held skeptical beliefs about education science: On average, they perceived educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Diery et al (2020) underpin that student teachers are more skeptical about the benefits of educational sciences for practice than teacher educators. A recent study by Voss (2022) pointed in the same direction. This can be interpreted as an indicator that student teachers are not fully convinced of the usefulness of educational sciences.…”
Section: Introductionmentioning
confidence: 56%
“…Diery et al (2020) underpin that student teachers are more skeptical about the benefits of educational sciences for practice than teacher educators. A recent study by Voss (2022) pointed in the same direction. This can be interpreted as an indicator that student teachers are not fully convinced of the usefulness of educational sciences.…”
Section: Introductionmentioning
confidence: 56%
“…This rather requires -at best-controlled beforeafter studies. Some examples for such study designs can be found in the field of evidence-informed initial teacher education, of which some are represented in this special issue (e.g., Futterleib et al, 2022;Grimminger-Seidensticker and Seyda, 2022;Lohse-Bossenz et al, 2022;Voss, 2022). Further limitations of this study are, that the sample size at level 2, i.e., the school level, was too low to estimate complex models like the multilevel latent covariate model and multilevel multiple group models.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, these biases could have artificially inflated the variable relationships examined in this study. This possibility notwithstanding, students are often quite frank about their disregard for educational research, both in empirical studies (Peiser et al., 2022; Voss, 2022) and in personal interactions with teacher education faculty. Still, future studies could collect data on source use that is less prone to the above‐mentioned biases, such as analysing behavioural traces.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐service teachers often judge educational research as irrelevant because they deem it too detached from daily classroom practice (e.g. Voss, 2022); they struggle with the nature of scientific knowledge and are unsure about its implications and applicability (e.g. Ferguson et al., 2023).…”
Section: Introductionmentioning
confidence: 99%